2006
DOI: 10.1158/1535-7163.mct-05-0488
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines fused to antibodies and their combinations as therapeutic agents against different peritoneal HER2/neuexpressing tumors

Abstract: We have previously generated antihuman HER2/neuhumanized IgG3 fused to interleukin-2 (IL-2), IL-12, or granulocyte macrophage colony-stimulating factor (GM-CSF) [monofunctional fusion proteins (mono-AbFP)] or fused to IL-2 and IL-12 or IL-12 and GM-CSF [bifunctional fusion proteins (bi-AbFP)]. These AbFPs retained cytokine and antigen-binding activities. We have now further characterized the AbFPs and determined the heparinbinding activity of the fused cytokines, their ability to trigger IFN-; secretion and na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…This antibody-(IL-2) fusion protein retained the binding specificity of the antibody and cytokine biological activity similar to that of rhIL-2 [69]. We have also observed that anti-HER2/neu IgG3-(IL-2) retains the heparin-binding activity of IL-2 [70], a property that allows the binding of this cytokine to glycosaminoglycans present in the surface of cells [71] and that may play a role in the control of T-cell responses by IL-2 [72]. The authors explored the in vivo efficacy of anti-HER2 /neu IgG3-(IL-2) as a direct antitumor agent in a murine colon carcinoma cell line expressing human HER2/neu (CT26-HER2/neu), which was injected subcutaneously into immunocompetent syngeneic BALB/c mice.…”
Section: Antibody-(il-2) Fusion Proteinsmentioning
confidence: 54%
See 4 more Smart Citations
“…This antibody-(IL-2) fusion protein retained the binding specificity of the antibody and cytokine biological activity similar to that of rhIL-2 [69]. We have also observed that anti-HER2/neu IgG3-(IL-2) retains the heparin-binding activity of IL-2 [70], a property that allows the binding of this cytokine to glycosaminoglycans present in the surface of cells [71] and that may play a role in the control of T-cell responses by IL-2 [72]. The authors explored the in vivo efficacy of anti-HER2 /neu IgG3-(IL-2) as a direct antitumor agent in a murine colon carcinoma cell line expressing human HER2/neu (CT26-HER2/neu), which was injected subcutaneously into immunocompetent syngeneic BALB/c mice.…”
Section: Antibody-(il-2) Fusion Proteinsmentioning
confidence: 54%
“…Moreover, long-term survivors among mice challenged intraperitoneally with D2F2/E2 tumors retained significant protection after subcutaneous rechallenge with the same cell line more than 4 months later, and subsequent subcutaneous challenge with the parental cell line D2F2 not expressing human HER2/neu [70,124]. These results suggest that under these conditions, treatment with anti-HER2/neu (IL-12)-IgG3 could elicit a systemic long-term immune response and that this response could be expanded to antigens other than the targeted antigen [70,124]. In Section 5 the use of anti-HER2/neu (IL-12)-IgG3 in the context of prophylactic cancer vaccination is discussed.…”
Section: Antibody-(il-12) Fusion Proteinsmentioning
confidence: 96%
See 3 more Smart Citations